Omnipresent yet elusive: Teachers' views on contexts for teaching algorithms in secondary education. Issue 1 (2nd January 2021) - Nijenhuis-Voogt, Jacqueline; Bayram-Jacobs, Durdane; Meijer, Paulien C.; Barendsen, Erik
ABSTRACT: Background and Context: Although context-based teaching and learning has been investigated extensively in science education, little is known regarding the use of contexts for teaching CS in secondary education. Objective: The aim of this study was to examine the characteristics of contexts suitable for teaching algorithms and to investigate teachers' considerations regarding those contexts. Method: This study examines teachers' practices and reasoning concerning the use of contexts and is based on explorative, empirical research. Data were collected through semi-structured interviews with seven CS teachers and analyzed qualitatively. Findings: The results of this study reveal several characteristics of effective contexts for teaching algorithms and show teachers' ambitions to address the variation within the student population when selecting contexts that advance students' algorithmic thinking. Implications: The found characteristics may serve as recommendation for designing contexts. Development of teacher education and professionalization activities may benefit from the discussion of teachers' motives and concerns.